Coral-like NixCo1−xSe2 for Na-ion battery with ultralong cycle life and ultrahigh rate capability. Issue 8 (4th February 2019) - He, Yanyan; Luo, Ming; Dong, Caifu; Ding, Xuyang; Yin, Chaochuang; Nie, Anmin; Chen, Yanan; Qian, Yitai; Xu, Liqiang
Abstract : Coral-like Ni x Co1− x Se2 anode material with hierarchical architecture delivers ultralong cycle life and ultrahigh rate capability in SIBs. Abstract : Storage technology of electrical energy with ultrafast charge/discharge rates is in high demand for future electronics and electric vehicles. Among them, sodium ion batteries (SIBs) have received much attention, however, the exploration of electrode materials with a high rate capacity and long cycle life still faces great challenges. In this work, we have fabricated coralloid Ni x Co1− x Se2 with a hierarchical architecture for the first time, and it presents specific capacities of 321 mA h g −1 after 2000 cycles at 2 A g −1, corresponding to a capacity decay rate of 0.011% per-cycle, and 277 mA h g −1 even at the high rate of 15 A g −1, which could be attributed to the enhanced conductivity by Co-doping, the hierarchical architecture preventing the structure from collapsing or crushing, the accelerated electron transmission and the shortened diffusion distance of Na + . The extremely fast electron and Na ion transfer kinetics could be associated with the capacitive contribution. We further reveal the ultrastable and ultrahigh rate Na-ion storage mechanism through systematic analysis including compositional/structure evolution studies and comprehensive electrochemical characterizations. The presented strategy for the design and synthesis of coralloid, Co doped NiSe2 with a hierarchical architecture could enlighten researchers on the development of electrodes with an ultralong cycle life and ultrahigh rate capability.